Basanan dan Budaya Kopi di Banyuwangi - Edy Hariyadi (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2013)
This article discusses the coffee culture and basanan in Banyuwangi. The data in this article came froma variety of sources, i.e.: books, vcd of songs, interviews, direct observation, and video service, socialmedia, website, blog and search engines in the internet. Coffee and Banyuwangi culture has become anintegral and reflected in art and culture of Banyuwangi and the everyday life of the people ofBanyuwangi. The indigenous people or Using ethnic of Banyuwangi call coffee as wedang ireng. Itshows that they understand that the coffee is black, if not black is not coffee instead of its name. With acup of coffee, Using ethnic hope happy in heart.